Studi Potensi Pasir Sungai Di Sungai Rokan Sebagai Pasir Cetak Pada Pengecoran Logam - Sihite, Pernando; Masnur, Dedy; Badri, Muftil (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Rokan river is one of the the four biggest river in Province of Riau which contains abundant of sand. The utilization of the sand has not reached an optimum level due to the limits of information for optimal profitability with it is not documented and therefore it is used only for building’s materials. However some literatures indicate that the sand is suitable for foundry use based on the physical characteristics. In this paper, a laboratory investigations of four critical foundry properties; clay content, Grain Finest Number (GFN), moisture content, and permeability of the sand is conducted. The outcome of this research to determine the potency of Rokan river’s sand as molding sand in Sand Casting. The result shows all the samples are potential as the molding sand through certain treatments. The most potential river sand is  downstream river’s sand with the following characteriscs: clay content 1.29%, GFN 27.25, moisture content 1.35% and gas permeability 10.9564 cm/min while the upstream river’s sand:  clay content 1.24%, GFN 17.94, moisture content 1.31% and gas permeability 12.6524 cm/min.  Keywords: Rokan River Sand, Characterization